Prenatal Identification of a Novel Mutation in the MCPH1 Gene Associated with Autosomal Recessive Primary Microcephaly (MCPH) Using Next Generation Sequencing (NGS): A Case Report and Review of the Literature - Ioannis Papoulidis; Makarios Eleftheriades; Emmanouil Manolakos; Michael B. Petersen; Simoni Marina Liappi; Anastasia Konstantinidou; Maria Papamichail; Vassilios Papadopoulos; Antonios Garas; Sotirios Sotiriou; Ioannis Papastefanou; Georgios Daskalakis; et al. (Children, 2022)
Background: MCPH1 is known as the microcephalin gene (OMIM: *607117), of which the encoding protein is a basic regulator of chromosome condensation (BCRT-BRCA1 C-terminus). The microcephalin protein is made up of three BCRT domains and conserved tandem repeats of interacting phospho-peptides. There is a strong connection between mutations of the MCPH1 gene and reduced brain growth. Specifically, individuals with such mutations have underdeveloped brains, varying levels of mental retardation, delayed speech and poor language skills. Methods: In this article, a family with two affected fetuses presenting a mutation of the MCPH1 gene is reported. During the first trimester ultrasound of the second pregnancy, the measure of nuchal translucency was increased (NT = 3.1 mm) and, therefore, the risk for chromosomal abnormalities was high. Chorionic villi sampling (CVS) was then performed. Afterwards, fetal karyotyping and Next Generation Sequencing were carried out. Afterwards, NGS was also performed in a preserved sample of the first fetus which was terminated due to microcephaly. Results: In this case, the fetuses had a novel homozygous mutation of the MCPH1 gene (c.348del). Their parents were heterozygous for the mutation. The fetuses showed severe microcephaly. Because of the splice sites in introns, this mutation causes the forming of dysfunctional proteins which lack crucial domains of the C-terminus. Conclusion: Our findings portray an association between the new MCPH1 mutation (c.348del) and the clinical features of autosomal recessive primary microcephaly (MCPH), contributing to a broader spectrum related to these pathologies. To our knowledge, this is the first prenatal diagnosis of MCPH due to a novel MCPH1 mutation.